2012
DOI: 10.1111/j.1365-2486.2011.02619.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing carbon sequestration in temperate freshwater wetland communities

Abstract: High productivity and waterlogged conditions make many freshwater wetlands significant carbon sinks. Most wetland carbon studies focus on boreal peatlands, however, with less attention paid to other climates and to the effects of hydrogeomorphic settings and the importance of wetland vegetation communities on carbon sequestration. This study compares six temperate wetland communities in Ohio that belong to two distinct hydrogeomorphic types: an isolated depressional wetland site connected to the groundwater ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
126
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 231 publications
(133 citation statements)
references
References 58 publications
5
126
2
Order By: Relevance
“…Total carbon (TC, %) was analyzed by combustion at 900˝C. Samples for the determination of inorganic carbon (IC, %) were pre-treated with 10 mol¨L´1 H 3 PO 4 , then combusted at 200˝C, using standard procedures for wetland soils [42][43][44][45]. Total organic carbon (TOC) within each depth segment was calculated as the difference between TC and IC concentrations.…”
Section: Soil Carbon Analysismentioning
confidence: 99%
“…Total carbon (TC, %) was analyzed by combustion at 900˝C. Samples for the determination of inorganic carbon (IC, %) were pre-treated with 10 mol¨L´1 H 3 PO 4 , then combusted at 200˝C, using standard procedures for wetland soils [42][43][44][45]. Total organic carbon (TOC) within each depth segment was calculated as the difference between TC and IC concentrations.…”
Section: Soil Carbon Analysismentioning
confidence: 99%
“…Sedimentation has been measured with several methodologies, including: rare-earth stable tracer horizons like Cs-137 and Pb-210 (Craft and Richardson, 1993;Bernal and Mitsch, 2012), horizon markers (Knaus and Van Gent, 1989;Harter and Mitsch, 2003;Hupp et al, 2008), sediment traps and bottles (Mitsch et al, 1979a;Brueske and Barrett, 1994;Fennessy et al, 1994;Braskerud et al, 2000;Braskerud, 2001;Nahlik and Mitsch, 2008), dendrogeomorphic techniques (Hupp and Morris, 1990;Hupp et al, 1993), and sedimentation plates (Mitsch et al, 1979b;Braskerud et al, 2000;Braskerud, 2001). Variable methodologies have led to inconsistent and poorly comparable sedimentation rates.…”
Section: Introductionmentioning
confidence: 99%
“…Research also has shown that that estimating carbon sequestration rates for wetland catchments can be difficult, and published rates are highly variable and associated with a great deal of uncertainty (Euliss et al, 2006;Gleason et al, 2008;Kayranli et al, 2010;Badiou et al, 2011;Bernal and Mitsch, 2012;Mitsch et al, 2013). Gleason et al (2008) suggested that in addition to factors such as land-use history, restoration methods, soils, and time, carbon sequestration rates of restored PPR wetlands could be affected by climate.…”
Section: Ghg Mitigation Potential Of Wetland Restorationmentioning
confidence: 99%